Glucose transporters in cancer – from tumor cells to the tumor microenvironment. (25th June 2018) - Ancey, Pierre‐Benoit; Contat, Caroline; Meylan, Etienne
Abstract : Solute carriers of the glucose transporter (GLUT) family mediate the first step for cellular glucose usage. The upregulation of GLUTs has been reported in numerous cancer types as a result of perturbation of gene expression or protein relocalization or stabilization. Because they enable to sustain the energy demand required by tumor cells for various biochemical programs, they are promising targets for the development of anticancer strategies. Recently, important biological insights have come from the fine crystal structure determination of several GLUTs; these advances will likely catalyze the development of new selective inhibitory compounds. Furthermore, deregulated glucose metabolism of nontumor cells in the tumor mass is beginning to be appreciated and could have major implications for our understanding of how glucose uptake by specific cell types influences the behavior of neighboring cells in the same microenvironment. In this review, we discuss some of the deregulation mechanisms of glucose transporters, their genetic and pharmacological targeting in cancer, and new functions they may have in nontumor cells of the tumor environment or beyond glucose uptake for glycolysis. Abstract : This review summarizes our current knowledge on glucose transporter regulation and function in cancer. It highlights recent investigations on their fine structure determination, which could be critical for the development of inhibitory compounds. It also considers the complexity of the tumor microenvironment, where glucose transporters might contribute to cancer development beyond acting solely in tumor cells.